Sustainable consumption initiatives for bags, acceptance of the use of ecological straws, and legislation prohibiting the consumption of non-biodegradable straws in Brazil - Aguilar, Guilherme José; de Oliveira, Alan Maicon [UNESP]; Tapia-Blácido, Delia Rita (My University, 2024)
The replacement of traditional non-biodegradable plastic straws and bags with environmentally friendly and sustainable options emerges as an effective alternative to mitigate the environmental impacts resulting from improper disposal of these materials. However, the viability of this alternative is intricately linked to the acceptance of these products by the population, becoming crucial for the effective substitution and adoption of more sustainable habits. In order to understand the perspective of Brazilians regarding ecological consumption of drinking straw and bags, a survey was conducted in the city of Ribeirão Preto, São Paulo. Simultaneously, a survey of laws prohibiting the distribution of non-biodegradable plastic straws in Brazil was carried out. The results of this research revealed the acquisition of 354 valid questionnaires. The majority of respondents showed a favorable inclination towards adopting biodegradable straws and a more sustainable use of plastic bags. However, it was observed that, despite this predisposition, many still do not refuse these bags when offered in establishments. It is important to note that 17 Brazilian states already have legislation prohibiting the distribution of non-biodegradable straws by establishments. To build a truly sustainable future, it becomes imperative to combine environmental laws aimed at protecting the environment, raising awareness among the population, and promoting sustainable practices. These converging elements are crucial to favor the reduction of negative environmental impact and encourage the development of responsible consumption and production.
Iniciativas de consumo sostenible de bolsas, aceptación del uso de sorbetes ecológicas y legislaciones que prohíben el consumo de sorbetes no biodegradables en Brasil
Iniciativas de consumo sustentável de sacolas, aceitação do uso de canudos ecológicos e legislações de proibição do consumo de canudos não biodegradáveis no Brasil
Keywords: Brazil; Drinking straw; Plastic bag; Sustainable consumption